Rubber mixing process for improving the extrusion porosity of white carbon black mixed rubber

CN122956596APending Publication Date: 2026-10-23SHANDONG LINGLONG TIRE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611346105.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0002]白炭黑填充橡胶混炼胶是高性能轮胎胎面、高端工业橡胶制品的核心胶料,凭借白炭黑的补强特性可显著提升制品的抗湿滑性能、耐磨性能与低滚动阻力性能,在绿色轮胎领域已得到规模化应用;在螺杆压出加工过程中,胶料经螺杆强剪切捏炼后输送至机头,胶温通常可达90~140℃,机头顶压力超过5MPa;在此工况下,白炭黑表面羟基与硅烷偶联剂持续发生接枝反应,生成乙醇等小分子挥发物与水分,当胶料离开机头、压力骤降至常压时,内部残留的挥发物迅速汽化,在半制品断面形成气孔;同时压出过程中裹挟进入的空气无法及时排出,会进一步提升气孔率,高白炭黑、高补强炭黑填充体系的胶料该问题尤为突出;气孔缺陷不仅会导致压出尺寸波动、半成品合格率下降,还会影响后续硫化制品的力学性能与外观质量,大幅提升企业生产损耗与质量成本

Benefits of technology

1.本发明通过在母炼阶段适度降低转速、提升恒温反应温度,促进白炭黑与硅烷偶联剂在混炼阶段充分反应,使大部分挥发物在密炼机内提前释放排出,大幅减少胶料内部残留的挥发组分,从根源上降低压出过程中的气孔生成量,成品半制品断面气孔率下降显著。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956596A_ABST
    Figure CN122956596A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of rubber processing, and discloses a rubber mixing processing technology for improving the extrusion porosity of white carbon black mixed rubber, wherein the white carbon black mixed rubber contains 5-200 parts by weight of silicon dioxide and 5-90 parts by weight of carbon black based on 100 parts by weight of a rubber component, and the amount of a silane coupling agent is 0.5-20 wt% of the mass of the silicon dioxide; the rubber mixing processing technology comprises at least one stage of master batch process and one stage of final batch process. The application moderately reduces the mixing rotating speed and improves the constant temperature reaction temperature in the master batch stage, promotes the full completion of the grafting reaction of the white carbon black and the silane coupling agent in the internal mixing process, makes the small molecule volatile matter and moisture generated in the reaction release and discharge in advance, greatly reduces the residual volatile components in the rubber, and reduces the generation amount of pores in the extrusion process from the root; only the process parameters are adjusted, the extrusion equipment does not need to be replaced, no plasticizer needs to be additionally added, or the extrusion production speed does not need to be reduced, and the existing production line can be directly adapted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rubber processing technology, specifically a rubber compounding process for improving the porosity of silica compound. Background Technology

[0002] Silica-filled rubber compounds are core materials for high-performance tire treads and high-end industrial rubber products. Leveraging the reinforcing properties of silica, they significantly improve the wet skid resistance, abrasion resistance, and low rolling resistance of these products, and have already seen large-scale application in the green tire sector. During screw extrusion, the rubber compound is conveyed to the die head after being subjected to strong shearing and kneading by the screw. The rubber temperature typically reaches 90-140℃, and the die head pressure exceeds 5MPa. Under these conditions, the hydroxyl groups on the silica surface continuously undergo grafting reactions with the silane coupling agent, generating ethyl... Small volatile molecules such as alcohols and moisture rapidly vaporize when the rubber compound leaves the die head and the pressure drops sharply to atmospheric pressure, forming pores on the cross-section of the semi-finished product. At the same time, the air trapped in the extrusion process cannot be discharged in time, which further increases the porosity. This problem is particularly prominent in rubber compounds with high silica and high reinforcing carbon black filler systems. Porosity defects not only lead to fluctuations in extrusion dimensions and a decrease in the pass rate of semi-finished products, but also affect the mechanical properties and appearance quality of subsequent vulcanized products, significantly increasing production losses and quality costs for enterprises.

[0003] To address the aforementioned issue of extrusion porosity, the industry has implemented several technological improvements. For example, the patent CN114437423A, "A Low-Porosity Silica Compound and Its Preparation Method," introduces polyethylene glycol 4000 as a plasticizer to enhance the plasticity and flowability of the compound, thereby reducing porosity formation during extrusion. Other common industry improvement approaches include: 1. Replacing the screw extruder with one of a larger aspect ratio to increase plasticizing shear strength and promote volatile matter removal; 2. Reducing the speed of the extrusion production line to decrease air entrainment and extend the volatile matter release time; 3. Preheating and drying raw materials, extending the compound's dwell time, or employing a hot-feeding process to pre-remove moisture and low-molecular-weight volatiles from the raw materials.

[0004] However, the above solutions all have obvious technical limitations: 1. The solution of improving porosity by adding plasticizers will change the original formulation system, which will easily lead to a decrease in core indicators such as tensile stress and wear resistance of the rubber compound, and will not meet the performance requirements of high-performance products; 2. Replacing the extruder with a large aspect ratio requires a high investment in equipment modification costs, and the improvement in porosity is limited, and it cannot completely solve the porosity problem of the high silica-filled system; 3. Reducing the extrusion speed will directly reduce production efficiency and make it difficult to adapt to the needs of large-scale mass production; 4. Processes such as raw material preheating and drying and hot feeding will significantly increase production energy consumption, and excessively high feeding temperature will easily cause premature scorching of the rubber compound, posing production safety and quality risks; Therefore, developing a compounding process that can effectively reduce the extrusion porosity of silica compound without modifying production equipment, changing the main components of the formulation, or significantly increasing energy consumption and processing time is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a rubber compounding process that improves the porosity of silica compounded rubber, so as to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a rubber compounding process for improving the extrusion porosity of silica compound, wherein the silica compound, based on 100 parts by weight of rubber component, contains 5-200 parts by weight of silica and 5-90 parts by weight of carbon black, and the amount of silane coupling agent is 0.5-20 wt% of the silica mass; the rubber compounding process includes at least one masterbatch mixing step and one final rubber mixing step, specifically including the following steps: S1. First stage masterbatch: Set the initial speed of the internal mixer to 20~90 rpm. After the rubber components are added to the internal mixer and plasticized for 0~90 seconds, carbon black, silica, silane coupling agent, softener, activator, and antioxidant are added for mixing. After 1~5 steps of pressing operation, the mixture enters the constant temperature reaction stage. During the pressing operation, the speed of the internal mixer is reduced by 1~5 rpm, and the constant temperature reaction temperature is increased by 1~10℃ compared with the conventional mixing process. The constant temperature reaction temperature is controlled at 135~170℃, the constant temperature mixing time is 1~10 minutes, and the discharge temperature is controlled at 135~170℃. S2, Subsequent Masterbatch: The previous masterbatch rubber is fed into an internal mixer for at least one subsequent mixing stage. The rotation speed of each subsequent masterbatch stage is reduced by 1-5 rpm compared to the corresponding conventional mixing process. After completion, the masterbatch rubber is discharged. S3. Preparation of final compound: The final masterbatch is fed into an internal mixer, and vulcanizing agent and accelerator are added for final mixing. The final mixing speed is reduced by 1-5 rpm compared with the conventional final mixing process, and the discharge temperature is controlled not to exceed 110℃ to obtain the finished compound.

[0007] Preferably, in step S1, the pressing operation is carried out in four steps: the first step is to press and mix for 50~70s, the second step is to press and mix until the glue temperature is 130~140℃, the third step is to press and mix until the set constant temperature reaction temperature and then enter the constant temperature stage, and after the constant temperature is completed, the fourth step is to press and mix until the glue discharge temperature.

[0008] Preferably, the silane coupling agent in step S1 is at least one of bis-[3-(triethoxysilyl)propyl]tetrasulfide, bis-[3-(triethoxysilyl)propyl]disulfide, and γ-mercaptopropyltriethoxysilane.

[0009] Preferably, the softener in step S1 is at least one of aromatic oil, naphthenic oil, paraffin oil, and environmentally friendly aromatic oil; based on 100 parts by weight of rubber component, the amount of softener is 5 to 30 parts by weight.

[0010] Preferably, the activator in step S1 is a compound system of zinc oxide and stearic acid; based on 100 parts by weight of rubber component, the amount of zinc oxide is 2 to 5 parts by weight and the amount of stearic acid is 1 to 3 parts by weight.

[0011] Preferably, in step S2, the subsequent master refining is set in two stages, namely the second stage master refining and the third stage master refining; the initial speed of the second stage master refining is 30~35 rpm, and the speed during the mixing process is reduced by 1~3 rpm from the initial speed; the initial speed of the third stage master refining is 28~32 rpm, and the speed during the mixing process is reduced by 1~3 rpm from the initial speed.

[0012] Preferably, in the second stage of masterbatch mixing, carbon black is added to the first stage of masterbatch mixing, and after 2-3 steps of pressing and mixing, the discharge temperature is controlled at 135-145℃; in the third stage of masterbatch mixing, after 2-3 steps of pressing and mixing, the discharge temperature is controlled at 135-145℃.

[0013] Preferably, in step S3, the final masterbatch is first put into an internal mixer and mixed for 10-20 seconds, and then vulcanizing agent and accelerator are added; the pressing operation is carried out in 2-3 steps, with each pressing time being 10-20 seconds, and the final discharge temperature is controlled at 90-100℃.

[0014] Preferably, the total processing time for the entire mixing process is 800~900s, and the energy consumption for mixing per unit mass of rubber compound is 0.1~0.3kW・h / kg.

[0015] The beneficial effects of this invention are as follows: 1. This invention promotes the full reaction of silica and silane coupling agent during the mixing stage by appropriately reducing the rotation speed and increasing the constant temperature reaction during the master mixing stage. This allows most of the volatiles to be released and discharged in advance in the internal mixer, significantly reducing the amount of volatile components remaining in the rubber compound. This reduces the amount of porosity generated during the extrusion process from the source, resulting in a significant decrease in the porosity of the finished and semi-finished products.

[0016] 2. The present invention only adjusts the mixing speed and constant temperature parameters throughout the process. It does not require changing the extrusion equipment, adding additional plasticizers, or reducing the extrusion production speed. It can be directly adapted to existing production lines without changing the original rubber compound formulation system, thus avoiding the risk of performance degradation.

[0017] 3. In each stage of mixing, the rotation speed is only slightly reduced, the increase in constant temperature is controllable, and the total time and energy consumption of the entire mixing process are less than 15% different from the original conventional process. It will not significantly increase production costs, and takes into account both the improvement effect and production economy.

[0018] 4. The physical and mechanical properties of the compound prepared by this invention after vulcanization are less than 15% different from those of conventionally processed rubber compounds. While improving porosity, it can fully retain the core properties of the rubber compound such as wear resistance, tensile strength, and aging resistance, thus meeting the requirements for product use.

[0019] 5. This invention can effectively improve the dimensional stability of extruded semi-finished products, reduce the return rate of semi-finished products caused by porosity, reduce production losses and quality costs for enterprises, and is suitable for the production of various rubber materials such as tire treads filled with high-white carbon black and industrial rubber products. Attached Figure Description

[0020] Figure 1 This is a flow chart of the rubber compounding process for improving the porosity of silica compounded rubber according to the present invention. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] like Figure 1 As shown, this embodiment of the invention provides a rubber compounding process to improve the extrusion porosity of silica compound. It employs a typical high-silica-filled tread rubber formulation, based on a 100 phr rubber component, containing 38 phr silica and 27 phr silica. The silane coupling agent is used at 6.0 wt% of the silica mass. A four-stage compounding process (three stages of masterbatch + one stage of final compounding) is used, with specific process parameters as follows: 1. First stage master mixing (improved process): Raw rubber is put into the internal mixer and mixed at 50 rpm for 60 seconds; activator, antioxidant, silica, coupling agent and softener are added, and the speed is reduced to 35 rpm; the first step is to press and mix for 60 seconds, the second step is to press and mix to 135°C, the third step is to press and mix to 150°C and then enter the constant temperature reaction, which is maintained at 150°C for 230 seconds; after the end, the fourth step is to press and mix to 160°C to discharge the rubber.

[0023] 2. Second stage masterbatch (improved process): The first stage masterbatch rubber is put into the internal mixer, carbon black is added, and it is mixed at 31 rpm for 25 seconds; after the second step of pressing and mixing for 25 seconds and the third step of pressing and mixing for 15 seconds, the rubber is discharged at 140℃.

[0024] 3. Third stage masterbatch (improved process): The second stage masterbatch rubber is put into the internal mixer and mixed at 28 rpm for 25 seconds; after the second step of pressing and mixing for 25 seconds, the rubber is pressed and mixed to 140°C and discharged.

[0025] 4. Final rubber preparation (improved process): The three-stage masterbatch is fed into an internal mixer, vulcanizing agent and accelerator are added, and it is mixed at 25 rpm for 15 seconds; after the second step of pressing and mixing for 15 seconds and the third step of pressing and mixing for 15 seconds, the rubber is discharged at 95℃.

[0026] Comparative example (conventional process) Using the exact same formula as in the above embodiments, the conventional four-stage mixing process parameters are as follows: 1. First stage of masterbatch mixing: Mix raw rubber at 50 rpm for 60 seconds, add additives and reduce the speed to 40 rpm; first step of pressing and mixing for 60 seconds, second step of pressing and mixing to 135°C, third step of pressing and mixing to 145°C and then enter constant temperature reaction, maintain constant temperature at 145°C for 230 seconds; fourth step of pressing and mixing to 155°C and discharge the rubber.

[0027] 2. Second stage master mixing: Mix at 33 rpm for 25 seconds, then discharge the glue at 140°C after two-step pressing and mixing.

[0028] 3. Third stage master mixing: Mix at 30 rpm for 25 seconds, then discharge the glue at 135°C after two-step pressing and mixing.

[0029] 4. Final mixing: Mix at 27 rpm for 15 seconds, then press and mix in two steps before discharging the binder at 95°C.

[0030] The final rubber compounds prepared in the examples (improved process) and the comparative example (conventional process) were used to prepare semi-finished products under the same extrusion process conditions. The physical and mechanical properties of the rubber compounds after vulcanization, the porosity of the cross-section of the extruded semi-finished products, and the processing time and energy consumption of the entire mixing process were tested. The test results are shown in Tables 1 and 2 below.

[0031] Table 1. Comparison of properties of rubber compounds prepared by the improved process and the conventional mixing process.

[0032] Table 2 Comparison of mixing time and energy consumption between the improved process and the conventional mixing process

[0033] As shown in Table 1, before and after the process improvement, the differences in core performance indicators such as vulcanization characteristics, Mooney viscosity, scorch safety performance, density, and hardness of the rubber compound were all controlled within 5%, far below the fluctuation threshold of 15%, and all met the product standard requirements. It can be determined that the overall performance of the rubber compound before and after the improvement is comparable. Combined with the extrusion process verification, the compound prepared by the improved process of this invention has a porosity of more than 50% in the cross-section of the extruded semi-finished product compared with the conventional process, and the extrusion dimensional stability is significantly improved, effectively reducing the return rate of semi-finished products and production losses.

[0034] As shown in Table 2, the present invention improves porosity only by adjusting the mixing speed of each stage and the constant temperature reaction temperature of the first stage master refining, without adding any new processes or equipment; the difference in total mixing processing time is 5.1%, and the difference in total energy consumption is 1.4%, both of which are controlled within 10%, without significantly increasing production time and energy costs, taking into account both the quality improvement effect and production economy, and can be directly adapted to the existing production line for large-scale mass production.

[0035] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0036] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A rubber compounding process for improving the porosity of silica compound, characterized in that, The silica compound, based on 100 parts by weight of rubber components, contains 5-200 parts by weight of silica and 5-90 parts by weight of carbon black, with the amount of silane coupling agent being 0.5-20 wt% of the silica mass. The rubber compounding process includes at least one masterbatch mixing step and one final rubber mixing step, specifically including the following steps: S1. First stage masterbatch: Set the initial speed of the internal mixer to 20~90 rpm. After the rubber components are added to the internal mixer and plasticized for 0~90 seconds, carbon black, silica, silane coupling agent, softener, activator, and antioxidant are added for mixing. After 1~5 steps of pressing operation, the mixture enters the constant temperature reaction stage. During the pressing operation, the speed of the internal mixer is reduced by 1~5 rpm, and the constant temperature reaction temperature is increased by 1~10℃ compared with the conventional mixing process. The constant temperature reaction temperature is controlled at 135~170℃, the constant temperature mixing time is 1~10 minutes, and the discharge temperature is controlled at 135~170℃. S2, Subsequent Masterbatch: The previous masterbatch rubber is fed into an internal mixer for at least one subsequent mixing stage. The rotation speed of each subsequent masterbatch stage is reduced by 1-5 rpm compared to the corresponding conventional mixing process. After completion, the masterbatch rubber is discharged. S3. Preparation of final compound: The final masterbatch is fed into an internal mixer, and vulcanizing agent and accelerator are added for final mixing. The final mixing speed is reduced by 1-5 rpm compared with the conventional final mixing process, and the discharge temperature is controlled not to exceed 110℃ to obtain the finished compound.

2. The rubber compounding process for improving the porosity of silica compound as described in claim 1, characterized in that: In step S1, the pressing operation is carried out in four steps: the first step is to press and mix for 50~70s, the second step is to press and mix until the glue temperature is 130~140℃, the third step is to press and mix until the set constant temperature reaction temperature and then enter the constant temperature stage, and the fourth step is to press and mix until the glue discharge temperature is reached after the constant temperature is completed.

3. The rubber compounding process for improving the porosity of silica compound as described in claim 1, characterized in that: The silane coupling agent mentioned in step S1 is at least one of bis-[3-(triethoxysilyl)propyl]tetrasulfide, bis-[3-(triethoxysilyl)propyl]disulfide, and γ-mercaptopropyltriethoxysilane.

4. The rubber compounding process for improving the porosity of silica compound as described in claim 1, characterized in that: The softener mentioned in step S1 is at least one of aromatic oil, naphthenic oil, paraffin oil, and environmentally friendly aromatic oil; based on 100 parts by weight of rubber component, the amount of softener used is 5 to 30 parts by weight.

5. The rubber compounding process for improving the porosity of silica compound as described in claim 1, characterized in that: The activator mentioned in step S1 is a compound system of zinc oxide and stearic acid; based on 100 parts by weight of rubber component, the amount of zinc oxide is 2 to 5 parts by weight and the amount of stearic acid is 1 to 3 parts by weight.

6. The rubber compounding process for improving the porosity of silica compound as described in claim 1, characterized in that: In step S2, the subsequent master refining is set in two stages, namely the second stage master refining and the third stage master refining; the initial speed of the second stage master refining is 30~35 rpm, and the speed during the mixing process is reduced by 1~3 rpm from the initial speed; the initial speed of the third stage master refining is 28~32 rpm, and the speed during the mixing process is reduced by 1~3 rpm from the initial speed.

7. The rubber compounding process for improving the porosity of silica compound as described in claim 6, characterized in that: In the second stage of masterbatch mixing, carbon black is added to the first stage of masterbatch mixing. After 2-3 steps of pressing and mixing, the discharge temperature is controlled at 135-145℃. In the third stage of masterbatch mixing, after 2-3 steps of pressing and mixing, the discharge temperature is controlled at 135-145℃.

8. The rubber compounding process for improving the porosity of silica compound as described in claim 1, characterized in that: In step S3, the final masterbatch is first put into the internal mixer and mixed for 10-20 seconds, and then vulcanizing agent and accelerator are added; the pressing operation is carried out in 2-3 steps, with each pressing time being 10-20 seconds, and the final discharge temperature is controlled at 90-100℃.

9. The rubber compounding process for improving the porosity of silica compound as described in claim 1, characterized in that: The total processing time for the entire mixing process is 800~900s, and the energy consumption for mixing a unit mass of rubber compound is 0.1~0.3kW・h / kg.

Citation Information

Patent Citations

  • Rubber composition for reducing extrusion bubbles of semi-finished product and application

    CN114437423A